International criminal justice - Boas, Gideon; Chifflet, Pascale; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
What is international criminal justice? The authors of this book set out a framework for understanding international criminal justice in all its facets. Considering both definition and content, the authors argue for its treatment as a holistic field of study, rather than a by-product of international criminal law. Adopting a multidisciplinary approach, this book draws on a range of legal and extra-legal disciplines. Whilst addressing crucial legal questions throughout, it also considers the role and impact of politics, history, psychology, terrorism, transitioning society, and even the idea of hope in how we understand international criminal justice. Challenging many of the prevalent paradigms of thinking in this area, Gideon Boas and Pascale Chifflet explore whether it is possible to reconcile some of the enduring intellectual conflict, such as whether and how retributive and restorative approaches to justice can co-exist. Written by leading academics who themselves are also practitioners in the field, this unique work performs a significant role in defining and explaining international criminal justice, and as such will be important reading for scholars and practitioners, as well as providing an entry point for students in a classroom environment.
1. What is international criminal justice? -- 2. International criminal justice and history -- 3. International criminal justice and politics -- 4. International criminal justice and psychology -- 5. International criminal justice and responses to terrorism -- 6. International criminal justice and transitioning societies -- 7. International criminal justice and hope - some concluding remarks.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: mezinárodní právo trestní; trestní soudnictví; international criminal law; administration of criminal justice; e-knihy online; e-books online